Prevalence of intestinal parasitism of swine in a North Central State of Nigeria (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: Swine production is one of the most popular and promising livestock production industries in many parts of Nigeria. It prides itself in contributing to the supplementation of the overall national protein intake, gainfully engaging the citizenry in the industry and generating foreign exchange to the nation through export of produce and products. However, the swine production industry in Nigeria faced with religious and cultural constraints as well as several infectious diseases. The objective of this study was to investigate the prevalence of intestinal parasites in swine in the North Central State of Nigeria.Materials and methods: A total of 920 pigs comprising of 874 (95%) and 46 (5%) foreign and indigenous breed of pigs respectively were investigated in this study. Quantitative Mcmaster egg-counting technique was used for counting eggs of parasites. Semi-structured questionnaires was used to generate demographic data during October 2014 to March 2015.Results: Fifty five percent pigs were found to be positive for Hyostrogylus rubidus, while Ascaris suum, Trichuris suis and other unidentified eggs were present in 23, 17 and 5% pigs, respectively. Red Stomach Worm infection in swine was the highest parasitic burden observed as compared to other parasites. Spreading of infection within sexes had a P value of >0.5.Conclusion: The prevalence of parasites in pigs obtained in this work is a consequence of improper husbandry measures and irregular veterinary medical intervention.http://doi.org/10.5455/javar.2016.c163